Flow Cytometric Analysis and Sorting of Plant Chromosomes - Cápal, Petr; Said, Mahmoud; Molnár, István; Doležel, Jaroslav (Methods in molecular biology (Clifton, N.J.), 2023)
Flow cytometry offers a unique way of analyzing and manipulating plant chromosomes. During a rapid movement in a liquid stream, large populations can be classified in a short time according to their fluorescence and light scatter properties. Chromosomes whose optical properties differ from other chromosomes in a karyotype can be purified by flow sorting and used in a range of applications in cytogenetics, molecular biology, genomics, and proteomics. As the samples for flow cytometry must be liquid suspensions of single particles, intact chromosomes must be released from mitotic cells. This protocol describes a procedure for preparation of suspensions of mitotic metaphase chromosomes from meristem root tips and their flow cytometric analysis and sorting for various downstream applications.
Keywords: Cytogenetics; průtoková cytometrie; karyotypizace; Flow Cytometry; Chromosomes, Plant; cytogenetika; Accumulation of metaphase cells; Cytogenetic stocks; Chromosome isolation; chromozomy; Flow cytometry and sorting; Plants; Seedlings; Chromosomes; suspenze; Hydroponic; Suspensions; Karyotyping; Mitotic synchrony; FISH; FISHIS; chromozomy rostlin